2015
DOI: 10.1080/10705422.2015.1027801
|View full text |Cite|
|
Sign up to set email alerts
|

Making Service-Learning Partnerships Work: Listening and Responding to Community Partners

Abstract: This study explored community partners' perspectives regarding the motivations and barriers to engaging in service-learning partnerships. Three focus groups (N = 19) were held with representatives from diverse nonprofit organizations recruited from a university-based center for community service learning. Desire for expanded organizational capacity emerged as the strongest motivator, although enjoyment of mentoring students and the ability to acquire new knowledge also motivated individuals above and beyond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 19 publications
5
47
1
Order By: Relevance
“…We would also like to thank Kendra Schnarr for her review of the paper, Bronagh Ryan for her help with formatting and references, and two anonymous reviewers for their helpful comments and suggestions. Korzun et al 2014;Sandy and Holland 2006;Cronley et al 2015) also reports benefits, as does related service learning literature (see Taylor et al (2015) for a review). Further, there exists great potential for engaging in critical CES 3 as a way to produce and mobilize knowledge that more effectively addresses issues of justice-which are invariably imbedded in community resilience efforts-particularly for more marginalized communities (Da Cruz 2018).…”
Section: Strengths and Limitations Of Community-university Collaboratmentioning
confidence: 94%
“…We would also like to thank Kendra Schnarr for her review of the paper, Bronagh Ryan for her help with formatting and references, and two anonymous reviewers for their helpful comments and suggestions. Korzun et al 2014;Sandy and Holland 2006;Cronley et al 2015) also reports benefits, as does related service learning literature (see Taylor et al (2015) for a review). Further, there exists great potential for engaging in critical CES 3 as a way to produce and mobilize knowledge that more effectively addresses issues of justice-which are invariably imbedded in community resilience efforts-particularly for more marginalized communities (Da Cruz 2018).…”
Section: Strengths and Limitations Of Community-university Collaboratmentioning
confidence: 94%
“…Students are also the greatest source of immediate and tangible benefits: student labour frees up staff time and increases organisational capacity for new projects; students' ideas and energy bring fresh perspectives; student commitment to quality outcomes can inspire staff to reflect on their own work; students can introduce (and build confidence to use) new technology. (Cronley, Madden & Davis 2015;Gazley, Littlepage & Bennett 2012;Gerstenblatt 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While community groups typically enter into research relationships being promised mutually beneficial outcomes, studies show that academics and their institutions often benefit far more from these kinds of partnerships (Alcantara et al 2015;Bortolin 2011;Cronley, Madden & Davis 2015). For community partners, barriers to participating in CCE can include limited time and resources to fully engage (Keyte 2014;Lantz et al 2001), minimal support for building and maintaining partnerships (Dorow, StackCutler & Varnhagen 2011;Petri 2015;Sandy & Holland 2006), power imbalances (Schwartz et al 2016), lack of trust (Lantz et al 2001;Petri 2015) and high levels of staff and volunteer turnover (Keyte 2014;Schwartz et al 2016;Van Devanter et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For community partners, barriers to participating in CCE can include limited time and resources to fully engage (Keyte 2014;Lantz et al 2001), minimal support for building and maintaining partnerships (Dorow, StackCutler & Varnhagen 2011;Petri 2015;Sandy & Holland 2006), power imbalances (Schwartz et al 2016), lack of trust (Lantz et al 2001;Petri 2015) and high levels of staff and volunteer turnover (Keyte 2014;Schwartz et al 2016;Van Devanter et al 2011). Despite recognition of these challenges, institutional structures are typically designed to support academics (Cronley, Madden & Davis 2015;Dempsey 2010;Ward & Wolf-Wendel 2000). Studies have also identified significant barriers faced by academics when participating in CCE, including having limited time and resources and being discouraged from community-engaged pedagogies through tenure and promotion structures (Levkoe, Brial & Danier 2014).…”
Section: Introductionmentioning
confidence: 99%